An Ecotourism Quality Label for Maine? Insights from Sweden’s “Nature’s Best" Initiative - Vail, David (Maine Policy Review, 2004)
Nature-based tourism may be one way to revitalize lagging rural economies. David Vail offers “food for thought” based on Sweden’s recent development of an accreditation and branding process for eco-tourism operations. For an eco-tourism product to be awarded the label “Nature’s Best,” the operator must undergo a voluntary accreditation process which certifies that a set of quality standards has been met. Vail notes that effective marketing, ongoing financing, and demonstrated economic payoff both to operators and to local areas are key to determining the long-term success of Sweden’s “Nature’s Best” process. Like Sweden, he suggests, Maine may be able to capture an ecotourism market niche by establishing its own eco-tourism quality label.
Keywords: Maine; Sweden; tourism; eco-tourism; tourism qaulity label